HCI Beyond the GUI design for haptic, speech, olfactory, and other nontraditional interfaces / edited by Philip Kortum. - Kortum, Philip (Morgan Kaufmann Series in Interactive Technologies, 2008)
Create successful interface designs that use all five senses